ANALYSIS OF MULTICULTURAL EDUCATION VALUES IN THEMATIC TEXTBOOKS FOR PRIMARY SCHOOLS: A LITERATURE REVIEW - Didi Sudrajat; Fitria Meisarah; Dewi Anggraini (Adisam Publisher, 2025)
This study aims to analyse the values of multicultural education contained in thematic textbooks of elementary school through literature review. The method used is library research with content analysis technique on thematic textbooks of elementary school curriculum 2013 and other supporting literature. The results showed that the elementary thematic textbooks have integrated various multicultural values such as tolerance, pluralism, democracy, humanism, justice, and equality. These values are spread in various learning themes and subthemes, both explicitly and implicitly through stories, illustrations, and student activities. The integration of these multicultural values supports the creation of an inclusive and harmonious learning environment, and is relevant to the national education objectives to shape the character of learners who are able to coexist in a pluralistic society. However, there are still some values that are not evenly distributed throughout the themes, so continuous evaluation and development of thematic elementary textbooks are needed.